Non‐conventional fungicides to control dollar spot disease. Issue 1 (12th January 2021) - Hsiang, Tom; Stone, Kate; Rudland, Matt; Chen, Jie
Abstract: There are strong societal pressures against the use of synthetic pesticides in our modern urban society. The purpose of this work was to test the efficacy of several substances, many of which are household use items and can be considered non‐conventional, for their ability to control the common turfgrass disease, dollar spot, in lab and field tests. From the over 10 lab tests per treatment and the over 10 field tests between 2015 to 2019, we concluded that among over 20 mostly non‐conventional products applied at different rates and intervals, only ferrous sulfate (21% a.i.) used at 250 g per 100 m 2 or ferric sulfate (84.5% a.i.) used at 300 g per 100 m 2 applied in 10 L of water per 100 m 2 on a weekly basis could provide suppression of dollar spot disease on creeping bentgrass equivalent to a standard fungicide control during periods of low to moderate disease pressure.